Phylogenetic Analysis of K+ Transporters in Bryophytes, Lycophytes, and Flowering Plants Indicates a Specialization of Vascular Plants - Gomez-Porras, Judith L.; Riaño Pachón, Diego Mauricio; Benito, Begoña; Haro, Rosario; Sklodowski, Kamil; Rodríguez-Navarro, Alonso; Dreyer, Ingo (Frontiers in Plant Science, 2012)
As heritage from early evolution, potassium (K+) is absolutely necessary for all living cells. It plays significant roles as stabilizer in metabolism and is important for enzyme activation, stabilization of protein synthesis and neutralization of negative charges on cellular molecules as proteins and nucleic acids. Land plants even enlarged this spectrum of K+ utilization after having gone ashore, despite the fact that K+ is far less available in their new oligotrophic habitats than in sea water. Inevitably, plant cells had to improve and to develop unique transport systems for K+ accumulation and distribution. In the past two decades a manifold of K+ transporters from flowering plants has been identified at the molecular level. The recently published genome of the fern ally Selaginella moellendorffii now helps in providing a better understanding on the molecular changes involved in the colonization of land and the development of the vasculature and the seeds. In this article we present an inventory of K+ transporters of this lycophyte and pigeonhole them together with their relatives from the moss Physcomitrella patens, the monocotyledon Oryza sativa, and two dicotyledonous species, the herbaceous plant Arabidopsis thaliana, and the tree Populus trichocarpa. Interestingly, the transition of green plants from an aqueous to a dry environment coincides with a dramatic reduction in the diversity of voltage-gated potassium channels followed by a diversification on the basis of one surviving K+ channel class. The first appearance of K+ release (Kout) channels in S. moellendorffii that were shown in Arabidopsis to be involved in xylem loading and guard cell closure coincides with the specialization of vascular plants and may indicate an important adaptive step.